Peracetic Acid Treatment Generates Potent Inactivated Oral Vaccines from a Broad Range of Culturable Bacterial Species - Moor, Kathrin; Wotzka, Sandra Y.; Toska, Albulena; Diard, Médéric; Hapfelmeier, Siegfried; Slack, Emma (Frontiers in Immunology, 2016)
Our mucosal surfaces are the main sites of non-vector-borne pathogen entry, as well as the main interface with our commensal microbiota. We are still only beginning to understand how mucosal adaptive immunity interacts with commensal and pathogenic microbes to influence factors such as infectivity, phenotypic diversity and within-host evolution. This is in part due to difficulties in generating specific mucosal adaptive immune responses without disrupting the mucosal microbial ecosystem itself. Here we present a very simple tool to generate inactivated mucosal vaccines from a broad range of culturable bacteria. Oral gavage of 1010 peracetic acid-inactivated bacteria induces high-titer specific intestinal IgA in the absence of any measurable inflammation or species invasion. As a proof of principal, we demonstrate that this technique is sufficient to provide fully protective immunity in the murine model of invasive non-typhoidal Salmonellosis, even in the face of severe innate immune deficiency.